National Resilience Under Pressure: Indonesia’s Strategic Response To Indo-Pacific Geopolitical Competition - Ivan Rizky Apriharjadi; Puspitasari Puspitasari (Universitas Jenderal Ahmad Yani, 2026)
This article examines how Indo-Pacific geopolitical dynamics translate into concrete pressures on Indonesia’s national resilience and what policy responses are most plausible across the political, economic, and defense-security domains. It addresses a gap in the literature: studies on Indo-Pacific competition often remain separated from analyses of Indonesia’s national resilience and rarely integrate geopolitical structure, regional security interaction, and adaptive state capacity in a single framework. The study uses a qualitative literature-based design with a structured review of scholarly works, policy documents, and official statistical reports. The analysis applies framework analysis to trace causal pathways linking great-power rivalry, the South China Sea dispute, militarization, and regional economic interdependence to Indonesia’s resilience challenges. Because the study relies on secondary sources, it does not include primary interviews or subnational case evidence. The findings show that Indonesia is exposed to intensifying geopolitical competition through diplomatic pressure, supply-chain and investment vulnerability, and growing demands for maritime surveillance and defense modernization. At the same time, Indonesia’s strategic location also creates leverage through ASEAN-centred diplomacy, sea-lane connectivity, and issue-based cooperation. The article argues that strengthening national resilience requires not only adaptive diplomacy and maritime defense, but also economic diversification, institutional coordination, and a realistic recognition of policy trade-offs in responding to Indo-Pacific competition.